Intravenous Lipid Emulsion Therapy Does Not Improve Hypotension Compared to Sodium Bicarbonate for Tricyclic Antidepressant Toxicity: A Randomized, Controlled Pilot Study in a Swine Model. (November 2014) - Varney, Shawn M.; Bebarta, Vikhyat S.; Vargas, Toni E.; Boudreau, Susan; Castaneda, Maria; Olson, James E.
Abstract Objectives Tricyclic antidepressants (TCAs) are highly lipophilic medications used to treat posttraumatic stress disorder and chronic pain. Intravenous lipid emulsion (ILE) is a recent antidote for lipophilic drug overdose with unclear effectiveness. ILE has been studied in TCA overdose in small animals, and cases are reported in humans, but controlled studies in a larger animal model are lacking. Given the high lipophilicity of amitriptyline, a TCA, the hypothesis was that ILE would be more effective than the standard antidote sodium bicarbonate in improving amitriptyline‐induced hypotension. The objective was to determine if ILE improved hypotension (defined by a mean arterial pressure [MAP] < 60% baseline) compared to sodium bicarbonate for amitriptyline overdose in a critically ill porcine model. Methods In this prospective, randomized, controlled trial, 24 female Sus scrofa swine weighing 45 to 55 kg were infused with amitriptyline at 0.5 mg/kg/min until the MAP reached 60% of baseline values. Animals were randomized to the experimental treatment group (ILE 7 mL/kg bolus, then 0.25 mL/kg/min) or the standard treatment group (sodium bicarbonate 2 mEq/kg plus an equal volume of saline). The primary outcome was a 50% improvement in MAP after ILE administration. We continuously monitored heart rate (HR), systolic blood pressure (sBP), MAP, and cardiac output. Electrocardiograms were recorded every 15 minutes. Serum pH, pCO2, bicarbonate, lactate, and electrolytes were measured. Amitriptyline levels were measured by liquid chromatography/tandem mass spectrometry. Statistical methods used to detect a difference in MAP between the two treatment groups included repeated‐measures analysis of variance, adjusted for treatment, time, and the interaction of treatment by time. A sample size of 12 animals per group provided a power of 0.8 and an alpha of 0.05 to detect a 50% difference in MAP. Results There was no difference at baseline between ILE and sodium bicarbonate groups in mean HR, sBP, MAP, or cardiac output. Mean amounts of amitriptyline to reach hypotension and time to hypotension were similar between groups. After hypotension there was no difference between groups for mean HR, sBP, MAP, or cardiac output. The median time from hypotension to death was greater for the sodium bicarbonate group (10 minutes [IQR = 6 to 61 minutes] vs. 5 minutes [IQR = 4.5 to 6 minutes] for the ILE group; p = 0.003), but overall survival was not different. One ILE and four sodium bicarbonate pigs survived. Additionally, no difference was detected in QRS intervals between the two groups. The mean (±SD) amitriptyline level in the lipid layer was 3.34 (±2.12) μg/mL, and in the aqueous layer, 4.69 (±2.44) μg/mL. The ILE fatty layer contained 38.2% of total measurable amitriptyline, while the aqueous layer contained 53.6%. Conclusions Intravenous lipid emulsion treatment failed to improve amitriptyline‐induced hypotension when compared to the standard treatment of sodium bicarbonate in a large animal model of severe TCA overdose. Larger groups with better survival may yield different results from the high mortality observed in this pilot study. Similar amounts of amitriptyline were found in the aqueous and lipid layers. These conclusions are limited to a single ILE regimen.